Effect of wt% of Reinforcement on Tribological Properties of Epoxy/Al2O3 Polymer Nanocomposites - Tiwari, Himanshu; Singh, Sandip Kumar (International Journal of Membrane Science and Technology, 2023)
By using an immediate cross-linking procedure, five samples were created. Neat epoxy and epoxy filled with 0.5, 1.0, 1.5 and 2.0 wt% of Al2O3 nanorods. At four different sliding distances of 15, 30, 45 and 60 meters friction and wear tests were performed on all samples using a ‘linearly reciprocating ball on flat tribometer’ against an ASE 304 stainless steel counter surface at room temperature with a constant load of 15 N. It was found that when epoxy is reinforced with 2 wt% of Al2O3, the coefficient of friction decreases by 70% and volume loss decreases by 52% compared to that of pure epoxy for a total sliding distance of 60 meters. It was also found that as the wt% of Al2O3 nanorods increases in epoxy, average surface roughness decreases, resulting in a lower coefficient of friction. Scanning electron microscopic tests were also performed on all samples. It was found that epoxy containing 2.0 wt% of Al2O3 nanorods is smoothest among other images, which is evidence of wear resistance. It is the subject of further research what will happen if the wt% of Al2O3 nanorods in epoxy increases beyond 2 wt% but it is clear from this research that the minimum wt% of Al2O3 nanorods in epoxy should be at least 2 wt% to achieve efficient wear resistance.